2007
DOI: 10.4161/cc.6.17.4648
|View full text |Cite
|
Sign up to set email alerts
|

Bacterially-Derived Nanocells for Tumor-Targeted Delivery of Chemotherapeutics and Cell Cycle Inhibitors

Abstract: Chemotherapeutic drug therapy in cancer is seriously hampered by severe toxicity primarily due to indiscriminate drug distribution and consequent collateral damage to normal cells. Molecularly targeted drugs such as cell cycle inhibitors are being developed to achieve a higher degree of tumor cell specificity and reduce toxic side effects. Unfortunately, relative to the cytotoxics, many of the molecularly targeted drugs are less potent and the target protein is expressed only at certain stages of the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 90 publications
0
32
0
Order By: Relevance
“…Nevertheless, active targeting might significantly decrease the effective dosing required for antitumor efficacy. For example, MacDiarmid et al (44, 45) reported that they were able to reduce i.v. doxorubicin doses required to achieve significant growth inhibition of murine breast cancer xenografts by more than 3 log scales when the drug was encapsulated in so-called “nanocells” coated with anti–epidermal growth factor receptor antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, active targeting might significantly decrease the effective dosing required for antitumor efficacy. For example, MacDiarmid et al (44, 45) reported that they were able to reduce i.v. doxorubicin doses required to achieve significant growth inhibition of murine breast cancer xenografts by more than 3 log scales when the drug was encapsulated in so-called “nanocells” coated with anti–epidermal growth factor receptor antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Benoit et al reported that the magnetotactic bacteria Magnetospirillum magneticum AMB-1 could produce positive MRI contrast and colonize mouse tumor xenografts, providing a potential tool for MRI visualization of bacteria in preclinical and translational studies to track cancer despite its lower sensitivity. Following IV injection of 64 Cu-labeled AMB-1, PET imaging also revealed increased bacterial colonization of tumors, but decreased colonization of other organs, such as liver and spleen, after 4 h [57].…”
Section: Bacteriamentioning
confidence: 98%
“…These minicells can be packaged with therapeutically relevant concentrations of a range of therapeutics and selectively targeted to cancer cells via bispecific antibodies (BsAbs) (Fig. 1d) [64,65]. A two-wave cancer treatment has been explored in which minicells are specifically and sequentially delivered to tumor xenografts.…”
Section: Bacteria-like Particlesmentioning
confidence: 99%
“…In parallel to developing novel targeting ligands, novel nanocarrier compositions have also been extensively investigated in the past decade, e.g., minicells (MacDiarmid et al 2007a, 2007b), apotransferrin (Krishna et al 2009) and synthetic HDL or LDL lipid nanoparticles (Nikanjam et al 2007, Thaxton et al 2009). Moreover, inorganic drug delivery systems such as nanodiamond and single wall carbon nanotube also demonstrated some potential (Bhirde et al 2009, Lam and Ho 2009).…”
Section: Novel Delivery Strategies For Targeted Nanocarriersmentioning
confidence: 99%
“…MacDiarmid et al (2007a, 2007b, 2009) described a new type of nanocarrier known as minicells. These are ~400 nm in diameter and are derived from achromosomal bacterial cells.…”
Section: Novel Delivery Strategies For Targeted Nanocarriersmentioning
confidence: 99%